Bridging Ideology and Practice: A Policy Analysis of Pancasila Economy in Empowering Local MSMEs in Indonesia - Ikhsan, Muhammad Miftahul; Rasyid, Fauzan Ali; Saleh, Chaerul; Fadillah, M Rizki (CV. Strata Persada Academia, 2025)
Policies from political economy can have an overall impact on the state system, This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. Emil Salim explained the characteristics of the economy based on Pancasila having a role, state and private businesses go hand in hand that can avoid monopoly. The economy of Pancasila is based on the principle of family. Society can be an important role, no longer moving individually. The state has a role to control natural resources but must be based on the implementation of rights and obligations with a maximum plan. Pancasila economy is a people-based economy where the community gets the core of the five precepts in the economy. The causes of MSMEs with local products are difficult to develop, namely: Limitations with financial access. Minimal distribution network. Managerial skills that have not been maximized. Fierce market competition. Limited infrastructure. Requires mentoring and training. Weak Marketing and Branding. Steps that can be used as recommendations are: providing easy access to capital. Provide training assistance, business managerial, marketing, branding. The government becomes a promotional medium to echo local products. The need for triplehelix cooperation between the government, society, media to echo local products. forming a tagline, by providing a promotional platform with local products.